Recursos pascícolas de la dehesa extremeña. Primeros datos para la modelización de su gestión - González, F; Murillo, M; Paredes, J; Prieto, P M (Pastos, 2007)
The ecosystem “Dehesa” is considered as a good example of balance between the use of natural resources and the preservation of environmental values, therefore, its study requires special consideration. One important aspect to take into account to handle this ecosystem is the management of pastures and their production. In order to develop a decision support tool for the integrated management of the “dehesa”, a total of 52 farms spread throughout Extremadura are being surveyed to measure yield and botanical composition of their pastures. The information taken from 2004 to 2007 is summarized in this paper
Keywords: distribution; Pasture legumes; production

PROCESADO DE LABORATORIO PARA LA OBTENCIÓN DE LOS PARAMETROS CARACTERISTICOS DEL CORCHO EN PLANCHA - González, F; GONZÁLEZ, J R; de la Vega, R; Cristóbal, A (III Congreso Forestal Español, 2001)
We enumerate a register of trials and laboratory operations to process pluggings from probes and cork planks in general. We also set the cheracteristic parameter before and after heating and the formula to calculate them is shown
Keywords: Characteristic parameter; Cork; Quality

VARIABILIDAD DE LOS PARAMETROS CARACTERÍSTICOS DEL CORCHO EN PLANCHA CON LA ALTURA DE EXTRACCIÓN - González, F; GONZÁLEZ, J R; GARCIA DE CECA, J L; GONZÁLEZ, M (III Congreso Forestal Español, 2001)
135 cork sample planks have been gotten from 15 trees ready to uncork. Planks were taken from 5 different heights and 2 orientations. 12 variables have been measured and studied from them. The following variables show a decrease in their values with the extraction height: Yearly average growth in thickness and superficial density before and after boiling. Two groups based on the sampling average height of 130 cm can be made with the following variables: thickness expansion, visual quality and coefficient of porosity. With few exceptions, the quality index (QI) shows a bigger commercial value for the cork coming from the upper part of the debarking height
Keywords: Characteristic parameter; Cork; Quality